A DFT study or the relationship between the electronic structure and the antiplasmodial activity of a series of 4-anilino-2-trichloromethylquinazolines derivaties - ANATOVI, Wilfried; KPOTIN, ASSONGBA GASTON; KUEVI, URBAIN AMAH; KPOTA HOUNGUE, MAHOUGBE TATA ALICE; ATOHOUN, YACOLÈ GUY SYLVAIN; MENSAH, JEAN-BAPTISTE (My University, 2017)
A theoretical study of the relationships between the electronic structure and the antiplasmodial activity of a series of 4-anilino-2-trichloromethylquinazolines derivatives on plasmodium genes was carried out. The electronic structure of molecules was calculated at the B3LYP/6-31G(d,p) level with full geometry optimization. A statistically significant equation (R = 0.98, R² = 0.96, adj-R² = 0.94, F (12, 20) = 43.49 (p < 0.000001) and SD = 0.12) was obtained relating the variation of the biological activity with the variation of a set of local atomic reactivity indices. Based on the analysis of the results, a two-dimensional antiplasmodial pharmacophore was proposed. The process seems to be orbital and charge controlled.
Keywords: antiplasmodial; DFT; QSAR; KPG method; 4-anilino-2-trichloromethylquinazolines